Viewing the Kenyan health system through an equity lens: implications for universal coverage - Chuma Jane; Okungu Vincent (BMC, 2011)
Abstract Introduction Equity and universal coverage currently dominate policy debates worldwide. Health financing approaches are central to universal coverage. The way funds are collected, pooled, and used to purchase or provide services should be carefully considered to ensure that population needs are addressed under a universal health system. The aim of this paper is to assess the extent to which the Kenyan health financing system meets the key requirements for universal coverage, including income and risk cross-subsidisation. Recommendations on how to address existing equity challenges and progress towards universal coverage are made. Methods An extensive review of published and gray literature was conducted to identify the sources of health care funds in Kenya. Documents were mainly sourced from the Ministry of Medical Services and the Ministry of Public Health and Sanitation. Country level documents were the main sources of data. In cases where data were not available at the country level, they were sought from the World Health Organisation website. Each financing mechanism was analysed in respect to key functions namely, revenue generation, pooling and purchasing. Results The Kenyan health sector relies heavily on out-of-pocket payments. Government funds are mainly allocated through historical incremental approach. The sector is largely underfunded and health care contributions are regressive (i.e. the poor contribute a larger proportion of their income to health care than the rich). Health financing in Kenya is fragmented and there is very limited risk and income cross-subsidisation. The country has made little progress towards achieving international benchmarks including the Abuja target of allocating 15% of government's budget to the health sector. Conclusions The Kenyan health system is highly inequitable and policies aimed at promoting equity and addressing the needs of the poor and vulnerable have not been successful. Some progress has been made towards addressing equity challenges, but universal coverage will not be achieved unless the country adopts a systemic approach to health financing reforms. Such an approach should be informed by the wider health system goals of equity and efficiency.